Individual Differences in Mental Accounting - Muehlbacher, Stephan; Kirchler, Erich (Frontiers in Psychology, 2019)
Individual differences in mental accounting have rarely been studied, and empirical evidence regarding the relation between mental accounting and personality characteristics is scarce. The present paper reports three studies applying a Likert-type scale to assess the extent individuals engage in mental accounting practices. In each study, the five items of the measure loaded on a single dimension and had acceptable reliability, with a Cronbach’s α between .72 and .77. Study 1 (N = 165) regards the mental processing of prior losses in the theater-ticket problem (Tversky and Kahneman 1981). Study 2 (N = 114) is based on prior work on income source effects (Fogel 1997) and analyzes mental accounting of prior gains. In both studies, individual differences in mental accounting moderated the effects of the experimental treatments. In an explorative survey conducted for Study 3 (N = 373), the extent of engaging in mental accounting was found to be positively correlated with being female, with conscientiousness, and financial literacy, and negatively related with education and non-planning impulsivity. Identification of individual differences and their correlates adds to existing evidence for some of the core assumptions of mental accounting theory. A practical implication of the findings is that providers of financial services must take individual differences into account when designing trainings and supportive tools for money management.